The Utopian Dilemma in the Western Political Imagination - Farrell, John (Taylor & Francis, 2023)
In this volume, John Farrell shows that political utopias-societies with laws and customs designed to short-circuit the foibles of human nature for the benefit of our collective existence-have a perennial opponent, the honor-based culture of aristocracy that dominated most of the world from ancient times into early modernity and whose status-based competitive psychology persists to the present day. While utopias aim at equality, the heroic imperative defends the need for personal and collective dignity. It asks the utopian, Do we really want to live in a world without struggle, without heroes, and without the stories they create? Because the utopian dilemma pits essential values against each other-equity versus freedom, dignity versus justice-few who confront it can simply take sides. Rather, the dilemma itself has been a generative stimulus for classic authors from Plato and Thomas More to George Orwell and Aldous Huxley. Farrell follows their struggles with the utopian dilemma and with each other, providing a deepened understanding of the moral and emotional dynamics of the western political imagination.